Exploring fraudulent practices in Nigerian public sector: Evidence of Bauchi State / Shehu Umar Sa’id - Shehu Umar , Sa’id (2020)
The study explored fraudulent practices in the Nigerian public sector. This research aims to (1) explore conditions affecting fraudulent practices in Bauchi State, Nigeria. The study also aimed to (2) identify the challenges faced in preventing fraudulent behavior among Nigerian public employees. Most of the previous accounting studies on fraudulent practices focused on fraud prevention. Yet, accounting research so far considering various factors such as corporate governance, auditing, forensic audit, financial reporting regulation for fraud prevention and detection. To understand the conditions affecting fraudulent practices and the challenges faced in preventing fraud in the Nigerian public sector, a qualitative approach is employed in this study. The dynamic of the Fraud Diamond Theory assists in the collection of data. Semi-structure is conducted with 14 participants that comprise (4) Auditors, (4) Accountants, (2) Legal practitioners, (2) staff of Economic and Financial Crime Commission (EFCC), and (2) staff of Federal Inland Revenue Service. The interview data collected is analyzed using a thematic analysis approach. The research identified several possible conditions affecting fraudulent activities in the Nigerian public sector. The findings of this study indicate that (1) pressure, (2) opportunity, (3) rationalization, and (4) capability influence the employees to engage in fraudulent activities. In addition, the findings also show that (1) godfatherism, (2) lack of political will, (3) untrustworthy judges, and (4) political immunity are major challenges in preventing fraud in the Nigerian public sector. All these emanate from the poor corporate governance of the Nigerian public sector. The findings contribute to the body of knowledge by investigating fraudulent practices and challenges faced in preventing public mismanagement in the Nigerian public sector, evidence from the Bauchi State. Thus, the study provides an insight that could help to reduce the occurrence of fraud in the Nigerian public sector.